IDOLS IMMERSION – ENVIRONMENTAL POLLUTION - Murty, Dr. K. Krishna (IJRDO - Journal of Social Science and Humanities Research, 2017)
There is ample evidence to prove that the society in ancient times paid more attention to the protection of environment than what we think at present. Nature is God and God is Nature. That’s how our ancient sages and wisemen treated our natural environment in all her glory. Ancient civilization has never sacrificed nature to speculation, but holding it has divine, has honored her natural beauties by the erection of works of art. Solace of nature is what they had uppermost in their minds, which we too despite the past face of modern life should aim to imbibe. On the other hand, rapid economic development software, technological and scientific advancements have increased their impact on the natural environment, famous ecologist Edward Goldsmith said, “By now it should be clear that the environment becoming less capable of sustaining the growing impact of our economic development” It was ‘dharma’ of each and every individual in the society to protect the nature. The people in ancient times worshipped the objects of the nature. In the ancient times the trees, water, land and animals gained important position. For causing injury to plants different punishments were prescribed Govindaraja makes a distinction between injury to shade-giving plants, flower-bearing plants and fruit-bearing plants and he prescribes the lowest, middle and highest immurements respectively. Kautilya went a step further and fixed the punishment on the basic importance on the part of the tree. Manu imposes duty on mankind to protect the forests. On the other hand we are running blindly behind economic advancement selfishly without considering about the future of the future generation as rapid economic development technological and scientific advancements have increased their impact on the natural environment.